Avaliação do consumo alimentar de trabalhadores em turnos da área da enfermagem - Pires, Karina Bueno (2014)
Introduction: Studies suggest that the high incidence of poor dietary habits in shift workers may be associated with a greater incidence of disease. However, the lack of appropriate methodologies in studies that have evaluated the food intake patterns of this group of individuals is evident. Objective: To assess the macro and micronutrient intake of nursing professionals working different shifts. Methods: Two hundred and twenty two nursing workers were classified into three shifts: day shift (n=112), who worked only during the day (morning or afternoon without night shift); night shift (n=55), who worked only during night shifts; and day-night shift (n=54), who worked during the day (morning or afternoon) plus at least 9 hours a week of night shifts. Volunteers underwent nutritional assessments (24-hour recall on three non-consecutive days, including one day on the weekend) and evaluations of anthropometric variables (weight, height, body mass index and waist circumference) and sleep pattern (Epworth Sleepiness Scale). The food intake assessment was performed by comparison with the reference values recommended by the Dietary Reference Intakes (DRIs). Results: The total time of hours worked per week was significantly higher in the night and day-night shift compared to day shift (p <0.0005). The average sleep time during the working days (minutes) was lower in the night shift compared to day and day-night shift (p <0.0005). Daytime sleepiness was higher in the night shift, when compared to the day and day-night shift (p <0.02). In general, the percentage intake of macronutrients, in relation to caloric intake, was adequate in three groups. An increased consumption of protein and fat was observed in the night workers when compared to the day-night and day workers (protein: 21.2 ± 0.8, 18.2 ± 0.5, 18.1 ± 0.7, respectively, p = 0.01; fat: 35.5 ± 0.8, 32.5 ± 0.5, 31.1 ± 0.8, respectively; p = 0.001). Mean cholesterol intake was significantly lower in day-night workers compared to the day and night workers (188.1 ± 18.9, 239.2 ± 13.2, 248.0 ± 20.5, respectively; p = 0.04). Most workers analyzed showed a mean intake below the recommended allowances for vitamins and micronutrients, independent of the shift work, besides a high frequency of inadequate vitamins and minerals of different adjustment ranges, considering the EAR and RDA values, regardless of the shift. Conclusion: We concluded that nurses working in shifts had adequate macronutrient intake but marked inadequacies in micronutrient intake, independent of the shift work.